Perception of the Jute Growers on Attributes of Innovation- CRIJAF SONA (Indian Journal of Extension Education, 2022)
To improve the quality of the jute fibres CRIJAF SONA was developed and disseminated by ICAR- Central Research Institute of Jute and Allied Fibres (CRIJAF). A study was carried out on 2021 in North 24 Parganas and Nadia districts respectively to assess the various aspects of CRIJAF SONA as perceived by the randomly selected 80 jute growers using structured interview schedule. The index values of perceived attributes of CRIJAF SONA for relative advantage, compatibility, complexity, observability and trialability were calculated as 93.87, 88.25, 43.08, 93.33 and 94.69 respectively. The technology effectiveness was found as 85.41 which shows that the technology is having favourable perception in selected jute growing areas.